1994
DOI: 10.1002/chin.199449273
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of 2‐Aminoimidazole Marine Metabolites: Clathrodine (X) and 3′‐Amino‐1′‐(2‐aminoimidazol‐4(5)‐yl)‐prop‐1′‐ene (XIII).

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hassner was the first to report the reaction of imidazole lithium with a vinyl azide, hydrolysis of the intermediate triazine gives the aminoimidazole [57]. Since that report, Potier has popularized the use of lithiated imidazoles [58]. Potier reported that lithiation with LDA followed by azide transfer from TsN 3 efficiently generated the 2-azidoimidazoles ( Fig.…”
Section: Direct Introduction Of N2mentioning
confidence: 99%
“…Hassner was the first to report the reaction of imidazole lithium with a vinyl azide, hydrolysis of the intermediate triazine gives the aminoimidazole [57]. Since that report, Potier has popularized the use of lithiated imidazoles [58]. Potier reported that lithiation with LDA followed by azide transfer from TsN 3 efficiently generated the 2-azidoimidazoles ( Fig.…”
Section: Direct Introduction Of N2mentioning
confidence: 99%